Antioxidants and Their Relationship with Polycystic Ovary Syndrome: a Review Study - Israa Ali Abdul Kareem Al-Samarai; Hanan N. Mohammed (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Polycystic Ovary Syndrome (PCOS) is a prevalent endocrine disorder among women of reproductive age, characterized by hormonal and metabolic imbalances that impair fertility and overall health. Specific Background: Recent studies have emphasized the crucial role of oxidative stress in PCOS pathogenesis, where excessive reactive oxygen species (ROS) and reduced antioxidant capacity lead to cellular and molecular damage. Knowledge Gap: Despite extensive research on PCOS, the mechanistic link between oxidative imbalance and PCOS progression, particularly the interplay between endogenous and exogenous antioxidants, remains insufficiently understood. Aims: This review aims to elucidate the relationship between oxidative stress and antioxidant systems in PCOS and to identify potential therapeutic roles of antioxidants in mitigating PCOS symptoms. Results: The synthesis of current findings demonstrates that antioxidant deficiency correlates with increased insulin resistance, ovulatory dysfunction, and chronic inflammation in PCOS patients. Supplementation with vitamins C and E, selenium, and metformin enhances oxidative balance, improves ovarian function, and reduces metabolic risks. Novelty: This study integrates biochemical, metabolic, and therapeutic perspectives on antioxidant-mediated modulation of PCOS. Implications: Strengthening antioxidant defenses presents a promising adjunctive strategy to traditional PCOS management, potentially improving reproductive outcomes and reducing long-term comorbidities Highlights: Oxidative imbalance contributes significantly to PCOS pathogenesis. Antioxidant therapy improves hormonal and metabolic regulation. Combining antioxidants with lifestyle changes enhances treatment outcomes. Keywords: Polycystic Ovary Syndrome, Oxidative Stress, Antioxidants, Insulin Resistance, Reproductive Health